Rabies infection and specific effect of vaccination in mice selected for high and low immunobiological parameters - Queiroz-da-Silva L.H.; De-Franco M.; Sant'Anna O.A (Brazilian Journal of Medical and Biological Research, 1997)
Innate and acquired resistance to rabies infection was investigated in mice genetically selected for high (H) or low (L) antibody responsiveness from selections I, III and IV and in mice selected for maximal (AIRmax) or minimal (AIRmin) acute inflammatory reaction. These mouse lines were infected intramuscularly with different virus dilutions and the LD50 was determined. The HIII and HIV mouse lines were more susceptible than the LIII and LIV lines and the HI line showed a discrete but higher resistance than the LI line. Analysis of the interline (H x L) F1 hybrids from selections III and IV indicated different dominance effects on the "resistant" and" susceptible" phenotypes when the route of vaccination was changed. No differences were observed between the AIRmax and AIRmin mice, suggesting that inflammation plays a minor role in the resistance to rabies virus. The comparison of LD50 in mice vaccinated by distinct routes showed that the highest interline difference occurred after intramuscular vaccination (250-fold between H and L and 800-fold between F1 and L). These results indicate that different mechanisms may participate in acquired antirabies resistance